2013
DOI: 10.1007/s10719-013-9504-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of distal sugars and interglycosidic linkage on the N-glycoprotein linkage region conformation: synthesis and X-Ray crystallographic investigation of β-1-N-alkanamide derivatives of cellobiose and maltose as disaccharide analogs of the conserved chitobiosylasparagine linkage

Abstract: The linkage region constituents, 2-deoxy-2-acetamido-β-D-glucopyranose (GlcNAc) and L-asparagine (Asn) are conserved in the N-glycoproteins of all eukaryotes. Elucidation of the structure and conformation of the linkage region of glycoproteins is important to understand the presentation and dynamics of the carbohydrate chain at the protein/cell surface. Earlier crystallographic studies using monosaccharide models and analogs of N-glycoprotein linkage region have shown that the N-glycosidic torsion, ϕN, is more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…These results suggest that the effect of interglycosidic linkage of disaccharide attached to threonine on the antibacterial activity is more pronounced than the nature of distal sugar of glycosylated analogs of these proline‐rich AMPs. Different configuration of interglycosidic linkages ( α or β ) are known to influence the N ‐glycosidic torsion angle at different extents in case of N ‐linked glycosides. It has been reported that small changes in carbohydrate composition are sufficient to induce conformational changes in the peptide .…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that the effect of interglycosidic linkage of disaccharide attached to threonine on the antibacterial activity is more pronounced than the nature of distal sugar of glycosylated analogs of these proline‐rich AMPs. Different configuration of interglycosidic linkages ( α or β ) are known to influence the N ‐glycosidic torsion angle at different extents in case of N ‐linked glycosides. It has been reported that small changes in carbohydrate composition are sufficient to induce conformational changes in the peptide .…”
Section: Resultsmentioning
confidence: 99%
“…Maltose is a primary disaccharide in the human diet, formed from two units of glucose joined with an alpha linkage. It is the second member of an important biochemical series of glucose chains ( 43 ). In the present study, the contents of shikimic acid, 1,4-dihydroxy-naphthoic acid, N-acetyl-D-galactosamine, trehalose, gentiobiose and xylose were decreased, while the maltose content was increased in the KOA group when compared with the control group, which may be related to the inhibition of the glycolysis and pentose phosphate pathways and increased blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%